Campus Canopy, 1945-02-17 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1945)
Spanish Dancers Will Appear Here -- Wide Awake Students Step into Spotlight With first Aid -- Claire Carson Is Named New ECA Chairman -- Sock and Buskin Club Selects "Cradle Song," Date March 9 -- Gift in Every Dormitory Beg "Won't You Be My Valentine"
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals